If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7y + -8)(y + -1) = 0 Reorder the terms: (-8 + 7y)(y + -1) = 0 Reorder the terms: (-8 + 7y)(-1 + y) = 0 Multiply (-8 + 7y) * (-1 + y) (-8(-1 + y) + 7y * (-1 + y)) = 0 ((-1 * -8 + y * -8) + 7y * (-1 + y)) = 0 ((8 + -8y) + 7y * (-1 + y)) = 0 (8 + -8y + (-1 * 7y + y * 7y)) = 0 (8 + -8y + (-7y + 7y2)) = 0 Combine like terms: -8y + -7y = -15y (8 + -15y + 7y2) = 0 Solving 8 + -15y + 7y2 = 0 Solving for variable 'y'. Factor a trinomial. (1 + -1y)(8 + -7y) = 0Subproblem 1
Set the factor '(1 + -1y)' equal to zero and attempt to solve: Simplifying 1 + -1y = 0 Solving 1 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1y = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1y = 0 + -1 -1y = 0 + -1 Combine like terms: 0 + -1 = -1 -1y = -1 Divide each side by '-1'. y = 1 Simplifying y = 1Subproblem 2
Set the factor '(8 + -7y)' equal to zero and attempt to solve: Simplifying 8 + -7y = 0 Solving 8 + -7y = 0 Move all terms containing y to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -7y = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -7y = 0 + -8 -7y = 0 + -8 Combine like terms: 0 + -8 = -8 -7y = -8 Divide each side by '-7'. y = 1.142857143 Simplifying y = 1.142857143Solution
y = {1, 1.142857143}
| (2b+1)(3b-1+4)= | | 3n-2n+4r= | | (5x+76)+(7x+200)=180 | | 14k-1= | | 9(2x-17)=72 | | 9(2x-17)=72 | | (2-4a)(9-5a)= | | -24=-16x^2+92x+24 | | -5y-4=26 | | -2x(2)+15x-11= | | .25(x)+.30(14)=.27(x+14) | | 3x-90=12 | | 3x-10=3x+13 | | g(x)=2x^2+3x-5g(x+2) | | 0=-16x^2+92x+48 | | (5x+148)+(7x+188)=180 | | 16-7x=-3+4 | | mx^2-5x+m=0 | | B^2+18+3b=0 | | X+y(2)=240 | | r-18=4 | | -84=3x | | (a+b)(5a-3b)= | | 30=-0.5x | | 4(x-2)=3(x) | | x+4=140 | | 3(1-7y)-14y=-7 | | 2x+3ifx=9 | | 3z=1-z | | -4(-4f-10)=3(2f-4)+2 | | 5(24.2)-32=89 | | f+k=z |